2005
DOI: 10.1002/ana.20392
|View full text |Cite
|
Sign up to set email alerts
|

Effective gene therapy for an inherited CNS disease in a large animal model

Abstract: Genetic diseases affecting the brain typically have widespread lesions that require global correction. Lysosomal storage diseases are good candidates for central nervous system gene therapy, because active enzyme from genetically corrected cells can be secreted and taken up by surrounding diseased cells, and only small amounts of enzyme (<5% of normal) are required to reverse storage lesions. Injection of gene transfer vectors into multiple sites in the mouse brain has been shown to mediate widespread reversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 35 publications
(54 reference statements)
2
101
0
Order By: Relevance
“…Two other clinical trials have tested AAV vectors carrying mammalian promoters such as the mouse phosphoglycerate kinase (PGK) promoter [120], or the rat neuron-specific enolase (NSE) promoter [121]. The choice of promoters is based on the availability of extensive data from pre-clinical studies in different animal models showing that AAV-mediated transgene expression under these promoters is stable and long lasting in the mammalian brain [122][123][124][125][126][127]. The stability of AAV gene expression in the human brain has been evaluated in clinical trials using an AAV2 vector encoding aromatic amino acid decarboxylase (AADC) injected into the putamen of Parkinson's disease patients [116], or children afflicted with AADC deficiency [115].…”
Section: Challengesmentioning
confidence: 99%
“…Two other clinical trials have tested AAV vectors carrying mammalian promoters such as the mouse phosphoglycerate kinase (PGK) promoter [120], or the rat neuron-specific enolase (NSE) promoter [121]. The choice of promoters is based on the availability of extensive data from pre-clinical studies in different animal models showing that AAV-mediated transgene expression under these promoters is stable and long lasting in the mammalian brain [122][123][124][125][126][127]. The stability of AAV gene expression in the human brain has been evaluated in clinical trials using an AAV2 vector encoding aromatic amino acid decarboxylase (AADC) injected into the putamen of Parkinson's disease patients [116], or children afflicted with AADC deficiency [115].…”
Section: Challengesmentioning
confidence: 99%
“…73 To test the efficacy of gene transfer, 8-week-old kittens affected with AMD received multiple intracranial injections of rAAV expressing the normal feline alpha-mannosidase cDNA. 74 The injections were performed at a time at which there was already clinical evidence of mild disease in the kittens. Physical and neurological examination after gene therapy revealed remarkable clinical improvement compared to untreated controls.…”
Section: Feline Modelsmentioning
confidence: 99%
“…Storage lesions were markedly reduced throughout the whole brain, despite the fact that in situ hybridization showed mRNA only around injections tracks. 74 …”
Section: Feline Modelsmentioning
confidence: 99%
“…12 The feline model has proved to be useful in the evaluation of experimental therapies including bone marrow transplantation and gene therapy. 13,14 Central nervous system (CNS) pathology in both human and feline AMD includes the accumulation of oligosaccharides within cells and the resultant swelling of neurons and glia. Myelin deficiency is found, though the mechanism for the deficiency has not been identified.…”
mentioning
confidence: 99%
“…[17][18][19] Previous studies have shown that the MTR could be used to monitor abnormal myelination in AMD cats and improvement in myelination following successful gene therapy. 12,14 However, magnetization transfer imaging was unable to detect significant differences in gray matter between affected and normal cats. 12 Magnetization transfer imaging may also have limited application due to associated high radio-frequency power deposition, which can lead to excessive tissue heating, which can be unacceptable from an MR imaging-safety standpoint.…”
mentioning
confidence: 99%